2003
DOI: 10.1177/0310057x0303100408
|View full text |Cite
|
Sign up to set email alerts
|

Propofol Alone, Sevoflurane Alone, and Combined Propofol-sevoflurane Anaesthesia in Electroconvulsive Therapy

Abstract: Electroconvulsive therapy is an effective treatment for severe and medication-resistant depression. There have been no reports describing how a volatile anaesthetic affects haemodynamic responses, seizure duration, and recovery characteristics during electroconvulsive therapy. We carried out a repeated-measure crossover study to compare the effects on haemodynamic responses, seizure duration, and recovery characteristics of the following types of anaesthesia in electroconvulsive therapy: propofol alone, sevofl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
3
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 23 publications
1
35
3
1
Order By: Relevance
“…Hemodynamic alteration under propofol anesthesia is more stable than that under barbiturate anesthesia [46][47][48]. Additional use of sevoflurane has been proposed to blunt the hemodynamic activation during ECT [49], although it requires a relatively long induction time and induces relatively short seizure.…”
Section: Recommended Medication Protocols (Anticholinergic and Antihymentioning
confidence: 99%
See 2 more Smart Citations
“…Hemodynamic alteration under propofol anesthesia is more stable than that under barbiturate anesthesia [46][47][48]. Additional use of sevoflurane has been proposed to blunt the hemodynamic activation during ECT [49], although it requires a relatively long induction time and induces relatively short seizure.…”
Section: Recommended Medication Protocols (Anticholinergic and Antihymentioning
confidence: 99%
“…Use of propofol [51] and supplemental use of lidocaine [36] or sevoflurane [49] also decrease seizure duration. However, recent psychiatric studies demonstrated that seizure duration is not necessarily related to therapeutic efficacy [52]; only abortive or extremely short seizures (of less than 15 s) are problematic [7].…”
Section: Recommended Medication Protocols (Anticholinergic and Antihymentioning
confidence: 99%
See 1 more Smart Citation
“…Four anaesthetics were selected and used according to common practice: isoflurane, propofol, ketamine and etomidate. These anaesthetics are widely used clinically, including for electroconvulsive therapy (ECT) (Hsieh et al, 1990;Gomez et al, 2001;Krystal et al, 2003;Wajima et al, 2003). However, seizure duration in ECT is usually transient whereas a suitable swine model for the evaluation of neuroprotectants should feature seizures of long duration.…”
Section: Na-induced Seizures and Anaesthesiamentioning
confidence: 99%
“…Wird Sevofluran als alleiniges Anästhetikum verwendet, können jedoch ausgeprägte hä-modynamische Reaktionen während der EKT auftreten. In Kombination mit Propofol ist die Herz-Kreislauf-Funktion stabiler, allerdings unter Inkaufnahme einer kürzen Krampfdauer [65].…”
Section: Sevofluranunclassified